2020
DOI: 10.1016/j.envint.2020.106050
|View full text |Cite
|
Sign up to set email alerts
|

Combined exposure to formaldehyde and PM2.5: Hematopoietic toxicity and molecular mechanism in mice

Abstract: PM 2.5 and formaldehyde (FA) are major outdoor and indoor air pollutants in China, respectively, and both are known to be harmful to human health and to be carcinogenic. Of all the known chronic health effects, leukaemia is one of the most serious health risks associated with these two pollutants. To explore the influence and underlying mechanisms of exposure to formaldehyde and PM 2.5 on hematopoietic toxicity, we systematically studied the toxicity induced in hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 65 publications
4
17
0
Order By: Relevance
“…A study on mice found that PM 2.5 could induce epithelial damage and inflammatory cell infiltration, and there was an imbalance of Th1/Th2 . A research also found increased immune system disorder with the destroyed balance of Th1/Th2 in PM 2.5 -treated mice . In our study, the results showed that T-bet and GATA3 expression had a negative correlation with PM 2.5 exposure.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A study on mice found that PM 2.5 could induce epithelial damage and inflammatory cell infiltration, and there was an imbalance of Th1/Th2 . A research also found increased immune system disorder with the destroyed balance of Th1/Th2 in PM 2.5 -treated mice . In our study, the results showed that T-bet and GATA3 expression had a negative correlation with PM 2.5 exposure.…”
Section: Discussionsupporting
confidence: 63%
“…15 A research also found increased immune system disorder with the destroyed balance of Th1/Th2 in PM 2.5 -treated mice. 37 In our study, the results showed that T-bet and GATA3 expression had a negative correlation with PM 2.5 exposure. Our results indicated that with the PM increasing, the Th1 expression was more inhibited than Th2.…”
Section: Discussionsupporting
confidence: 52%
“…It has been suggested that PM 2.5 and formaldehyde might induce hematopoietic toxicity by reducing the expression of blood cells, myeloid progenitor cells (MPCs) and hematopoietic growth factors. In addition, PM 2.5 increased DNA damage and oxidative stress by disrupting the balance of Treg/Th17 and Th1/Th2 and suppressing the DNA-repair related mTOR pathway [ 194 ].…”
Section: The Effects and Mechanisms Of Pm On Neurologic Systemmentioning
confidence: 99%
“…Nevertheless, it is also associated with reports of toxicity and permanent harmful damage to embryos and chicks when applied to hatching eggs ( Table 1 ). Although these effects depend on the concentration, length of time and method of application of formaldehyde and the period in which the egg is exposed [ 13 ], formaldehyde itself is carcinogenic because it impairs and inhibits DNA repair [ 30 ]. Therefore, its use is unjustifiable regarding embryonic life safety, health and protection.…”
Section: Sanitizers and The Sanitization Of Hatching Eggsmentioning
confidence: 99%